2018
DOI: 10.1159/000488198
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Exposure Factors for Various Breast Composition and Thicknesses in Digital Screening Mammography Related to Breast Dose

Abstract: Objective: To investigate the effect of exposure factors used in digital screening mammography on image quality of different breast compositions. Material and Methods: A digital mammography unit, with tungsten (W) as target, rhodium (Rh) and silver (Ag) as filters, and amorphous selenium detectors, was used to image Computerized Imaging Reference Systems (CIRS) Model 12A phantoms of thickness 4, 5, and 6 cm. Images of each phantom were obtained using target-filter combinations of W/Rh and W/Ag, at 28, 30, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The previous studies have shown that the W/Rh combination is always the optimum choice to deliver high performance in terms of image quality at a lower dose, [ 20 , 21 ] but they did not specify the breast thickness. The CNR for a 34 kV Rh filter was significantly better than that for other kV values ( P = 0.027).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have shown that the W/Rh combination is always the optimum choice to deliver high performance in terms of image quality at a lower dose, [ 20 , 21 ] but they did not specify the breast thickness. The CNR for a 34 kV Rh filter was significantly better than that for other kV values ( P = 0.027).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] There are reports of using the W/Rh combination for compressed breast thicknesses ranging from 4 to 6 cm and different breast glandularities, which delivered high performance in terms of image quality at a lower radiation dose. [ 20 , 21 ] The main aim of this study was to determine the effects on the image quality and radiation dose of different combinations of target/filter materials with various settings of the X-ray tube voltage. Two DM imaging systems were used on a 6 cm thickness equivalent breast phantom containing materials equivalent to 20% glandular tissue and 80% adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation dose is cumulative over time, so it is prudent to limit exposure to DBT. A further dose reduction can be achieved by using a target/filter combination of tungsten/rhodium as suggested recently [28]. As we mentioned previously, DBT has already been implemented in Kuwait for the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable of these drawbacks is that some of the malignancies may be missed or misinterpreted; there is a restricted opportunity to image microcalcification and there is a concern with the radiation dose. 23 26 In addition, in Kuwait, digital breast tomosynthesis (DBT) is not used as a screening tool. Despite DBT having a few drawbacks, several authors are investigating the possibilities of using it effectively in screening.…”
Section: Discussionmentioning
confidence: 99%